Proceedings of a Hui held at Hirangi Marae, Turangi - Durie, M D (Victoria University of Wellington Law Review, 1995)
This article is a report based on the deliberations of a national Māori Hui held at the Hirangi marae, Turangi on Sunday 29 January 1995. Sir Hepi Te Heuheu called the Hui in response to the Government's Proposals for the Settlement of Treaty of Waitangi Claims and to consider how the rangatiratanga of Iwi might be advanced. The report discusses some preliminary considerations. The report then criticises the process adopted to develop the Proposal, including its lack of genuine consultation. The report then discusses the principles underlying the Proposal, the assumptions made by the Proposal, and the Proposal's settlement framework. An alternative approach is provided by the report, mostly focusing on constitutional change. The final part of the report contains substantive recommendations for the Crown.